Synthesis of superabsorbent carbonaceous kenaf fibre filled polymer using inverse suspension polymerisation - Munirah Ezzah, Tuan Zakaria; Saidatul Shima, Jamari; Suriati, Ghazali (Penerbit UMP, 2017)
This paper studies the synthesis of superabsorbent carbonaceous kenaf fibre filled polymer using inverse suspension polymerisation method. The kenaf fibre was prepared using the hydrothermal carbonisation process. Inverse suspension polymerisation process involved two different solution mixtures; a continuous phase containing cyclohexane, span-80, and kenaf fibre filler and a dispersed phase containing partially neutralised acrylic acid, acrylamide, initiator APS, and crosslinker NN-Methylenebisacrylamide. Kenaf fibre filler addition was varied with different weight percentages (0.01- 0.05 wt%). Water absorption testing using the teabag method showed sample containing 0.04 wt% carbon filler had the highest and optimal percentage of water absorbency, 55.27 g/g while the sample containing 0.01 wt% carbon filler displayed the lowest percentage of water absorbency, 45.27 g/g. All SPC samples showed a higher rate of water absorbency compared to SAP sample which had 40.61 g/g of average water absorbency. The samples were characterised by FTIR, FESEM - EDX, Mastersizer. All synthesised samples produced were in spherical beads form. It can be concluded that kenaf fibre affects the enhancement of superabsorbent polymer performance.